The Effect of Influence Job Environment, Job Characteristic, and Job Insecurity OF Burnout On Employee PT. Sandabi Indah Lestari. - Nefrielza Angela Putri; Tezar Arianto (Journal of Indonesian Management, 2024)
This research aims to determine the joint influence of job environment, job characteristics, job insecurity on burnout in PT employees. Sandabi Indah Lestari, both partially and simultaneously. The object of this research is PT. Sandabi Indah Lestari, totaling 92 respondents. In this research, the results of the multiple linear regression test showed that the regression equation obtained was as follows: Y = 8.265 + 0.680 (X1) + 0.320 (X2) + 0.227 (X3). Based on the multiple linear regression equation above, it can be interpreted that: The results of the study show that the Job Envinronment variable has a significant effect on Burnout at PT. Sandabi Indah Lestari, North Bengkulu. The research results show that the Job Characteristic variable has a significant effect on Burnout at PT. Sandabi Indah Lestari, North Bengkulu. The research results show that the Job Insecurity variable has a significant effect on Burnout at PT. Sandabi Indah Lestari, North Bengkulu. From the results of the tests that have been carried out, it can be concluded that the variables Job Envinronment, Job Characteristics and Job Insecurity have a significant effect on Burnout at PT. Sandabi Indah Lestari, North Bengkulu.